Answer 10
This is the formula of an arithmetic sequence.
a
n
=
a
1
+
d
(
n
−
1
)
a
n
=
a
1
+
d
(
n
-
1
)
Substitute in the values of
a
1
=
1
a
1
=
1
and
d
=
3
d
=
3
.
a
n
=
1
+
(
3
)
(
n
−
1
)
a
n
=
1
+
(
3
)
(
n
-
1
)
Simplify each term.
a
n
=
1
+
3
n
−
3
a
n
=
1
+
3
n
-
3
Subtract
3
3
from
1
1
.
a
n
=
3
n
−
2
B? <span>
1 2/3 </span><span>÷ 1 1/9 = 1.5
2.34 </span><span>÷ 0.6 = 3.9</span>
Answer: x = 15
Step-by-step explanation:
Vertical angles are equal so we can set 47 = 3x + 2
Now just solve the equation for x
47 = 3x + 2
Subtract 2 from each side
45 = 3x
Divide both sides by 3
15 = x
Answer:
8/9
Step-by-step explanation:
divide both by 4
Ok let’s say he folds N=14 so F would be the other q4